Healing while studying : reflections and strategies for healing, coping, and liberation of graduate students of minoritized identities - Williams, Richard, 1988- (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
Graduate students have seen a rapid and intense, often debilitating increase in experiences of burnout, political maneuvering placing their health, safety, and lives in risk, endured competing pandemics of racism, homophobia, transphobia, patriarchy, white supremacy, xenophobia, COVID-19, and ableism. Many have left the academy in conjunction with the Great Resignation (Serenko, A., 2022) in the United States, often without secure employment, excessive debt, and no plans for future study. Graduate students and scholars of higher education and mental health providers/practitioners are sounding alarms and noticing trends of decreased program enrollment (Hanson, 2022) and completion, leaving a rapidly growing and persisting number of vacancies in schools across the country (Hanson, 2022). Graduate students have expressed across platforms such as newspapers, social media, institutional media outlets, campus protests, and more feelings of hopelessness, devaluation of their professional and scholarly status, a dissolving sense of humanity, belonging, value, and appreciation within the academy. Graduate students with ancestry of global majority (Campbell-Stephens, 2021), including those with ancestry in the African Diaspora, Asian Diaspora, Latin Diaspora, and others that have historically been harmed or otherwise oppressed by white supremacy and colonization. The global majority has experienced white supremacy and colonization in conjunction with transgenerational burdens such as poverty, patriarchy, and theological (theological used in the Greek origin of Theos (God) and logos (word, reason, or plan)) oppression, that intensify the emotions described and are the primary contributors of this communal act of healing and liberation. Through these co-morbid pandemics, political and tangible warfare, and social isolation, there is a cohort of students that have demonstrated resolve, resilience, and have actively sought and created community. The Research, Advocacy, Collaboration, and Empowerment (R.A.C.E) virtual community that seeks to cultivate community and success of minoritized scholars of the global majority. Within R.A.C.E. Mentoring we have focused subgroups such as the Health and Spirituality with the intention of supporting, promoting and sharing wisdom, resources, and insight to help maintain a healthy lifestyle. This volume in the RACE Mentoring series, per the focus of RACE Mentoring health and spirituality group, includes examples of ways of coping, self-care, and healing that graduate implement in their personal, academic, and professional lives-- Provided by publisher.
Keywords: Minority graduate students -- United Sates.; Universities and colleges -- Graduate work -- Social aspects.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books